pH-responsive interface conversion efficient oral drug delivery platform for alleviating inflammatory bowel disease - Zhao, Yingying; Xu, Changqing; Liu, Qing; Lei, Xiaofei; Deng, Li; Wang, Fengyan; Yang, Jing (Frontiers in Chemistry, 2024)
A key challenge for the effective treatment of intestinal diseases, including inflammatory bowel disease (IBD), is to develop an oral drug delivery system that can resist gastric acid erosion and efficiently release drugs after rapid entry into the intestine. In the present work, we developed oral composite nanoparticles (MSZ@PRHS) consisting of a rough mesoporous silica (RHS) loaded with Mesalazine (MSZ) and a CAP polymer membrane for targeted relief of inflammation in colitis. At the pH values of the simulated stomach and small intestine, the release rate of MSZ from MSZ@PRHS was low, while at the pH values of the simulated colon, the release rate of MSZ was high. In dextran sulfate sodium salt (DSS)-induced acute colitis mouse model, compared with oral administration of the drug Mesalazine in the equivalent solution form, oral administration of PRHS loaded with drug-loaded nanoparticles can significantly alleviate the symptoms of inflammatory bowel disease, and improve the therapeutic effect. We propose that the intestinal microenvironment provides an interface for nanocomposites switch and a promising drug delivery platform for the management and treatment of many intestinal diseases, where controlled drug release and prolonged residence time are required.